The Effectiveness of Red Grape (Vitis vinifera) Seed and Skin Extract Treatment on Staphylococcus aureus Bacteria that Causes of Urinary Tract Infections in Pregnant Women Examined by using White Mice (Mus musculus) - Satriya Manggala Liastra; Ninuk Dwi Ariningtyas; Yelvi Levani (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Urinary tract infection or what is often called a UTI is an infectious disease of the urinary tract epithelium and is commonly caused by gram-positive bacteria, namely the Staphylococcus aureus, with a prevalence rate of 68 million patients in the world and 1.2 million patients in Indonesia. The diagnosis of UTI is established with a positive urine culture significance value ≥105 (CFU)/ml. The existing clinical management for cases of urinary tract infections in pregnant women uses amoxicillin to kill gram-positive bacteria, such as Staphylococcus aureus. However, there have been 469 cases of antibiotic resistance in pregnant women in Indonesia due to the non-compliance of using antibiotics for urinary tract infections. Vitis vinifera can be used as an alternative to natural bactericidal resveratrol containing anthocyanidin to kill gram-positive bacteria. This study used 28 white mice (Mus musculus) aged 6-21 weeks and weighing 120-200 grams injected with Staphylococcus aureus. The 28 subjects were divided into 4 groups, each of which consisted of 7 mice. The mice received K1 treatment with 250 mg/kgBW of amoxicillin and treatments with 200, 300, and 500 mg/KgBW red grape seed and skin extract. Before treatments were given, a pre-test was conducted to ensure that the results were not biased. Post-test was also performed after the Staphylococcus aureus injection, which was measured after 5 days of urine culture that reached 107 CFU/ml. The treatment in P3 using 500 mg/KgBW of red grape seed and skin extract contributed to the smallest result with 102 Cfu/ml, equals to the result produced by giving 250 ml/KgBW of amoxicillin.